The impact of urbanization on the development of tourism infrastructure in cities (Economics and region, 2024)
This article provides deep analysis the essence of the concept of «urbanization» and it’s impact on the development of tourism infrastructure. Reveals the main aspects of the relationships between the level of urbanizations of the country and the development of the tourism sector are disclosed, amphasizing that urbanization is an important incentive for the formation of a competitive tourist environment. The classification of countries by the level of urbanization allows us to identify specific models of tourism development in different regions of the world having their own unique characteristics and challenges. Particular attention is paid to a modern trands in urbanizations, in particular the rapid growth of the megacities, the development of infrastructure in the large cities and the integrations of innovative technologies into the urban environment. The article studies the impact of these processes on the tourism industry, including improving transport infrastructure, increasing the number of hotels, restaurant complexes, cultural, entertainment and educational facilities. The positive impact of the urbanization on the development of tourism infrastructure is considered, nothing the growth of opportunities for economic grows, cultural exchange and international cooperation. It is determined that effective management of urbanization processes contributes to the formation of favorable conditions for attracting tourists, expanding urban space for mass events and increasing the overall attractiveness on urban areas for tourist flows.
Keywords: urbanization; tourist infrastructure; smart-city; modernization of cities; transport infrastructure